Religion and medicine: A theoretical overview - Vanderpool, Harold Y. (Journal of religion and health, 1980)
Recent scholarly studies in history, sociology, anthropology, religion, and psychosomatic medicine, coupled with clinical experience in the care of patients, call for a reassessment of the interrelationships between religion and medicine. Six major areas of interaction between these forms of human experience are identified and outlined. Investigations into these interlinkages not only offer challenging new opportunities for discovery but also hold promise for the development of new, more effective forms of medical care and healing. This new understanding of the interconnections between medicine and religion has many implications both for health care practitioners and for professionals with specialized training in religious studies.